The AI book : the artificial intelligence handbook for investors, entrepreneurs and fintech visionaries - Chishti, Susanne, 1971- (Wiley, 2020)
"Written by prominent thought leaders in the global fintech investment space, The AI Book aggregates diverse expertise into a single, informative volume. Key industry developments are explained in detail, and critical insights from cutting-edge practitioners offer first-hand information and lessons learned. Coverage includes: Understanding the AI Portfolio: from machine learning to chatbots, from neurotrophic computing to natural language processing (NLP); a deep dive into the Machine Intelligence Landscape; essentials on core technologies, rethinking enterprise, rethinking industries, rethinking humans; quantum computing and next-generation AI. AI experimentation and embedded usage, and the change in business model, value proposition, organisation, customer and co-worker experiences in today's Financial Services Industry. The future state of financial services and markets -- what's next for the real-world implementation of AITech? The innovating customer -- users are not waiting for the financial services industry to work out how #AI can re-shape their sector, profitability and competitiveness. Boardroom issues created and magnified by AI trends, including conduct, regulation & oversight in an algo-driven world, cybersecurity, diversity & inclusion, data privacy, the 'unbundled corporation' & the future of work, social responsibility, sustainability, and the new leadership imperatives"--